2016
DOI: 10.1007/s00227-016-3030-8
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the dynamics of growth, development and lipid storage in the marine copepod Calanus finmarchicus

Abstract: Mechanistic models are essential tools for interpreting and predicting the consequences of a changing environment and stressors such as pollution on the life histories of marine organisms. Here, we apply the simple and generic energy-budget model DEBkiss to the life history of the marine copepod Calanus finmarchicus. Model modifications were needed to accommodate the copepod life cycle, which deviates in several respects from most other animals (e.g., a sudden stop of growth after the final moult). We identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 38 publications
0
30
0
1
Order By: Relevance
“… δ 13 C (‰) Location Source C3 producers −28.1 ± 2 84 C4 producers −13 ± 1.5 C3 producers −22 to −35 76 C4 producers −11 to −17 Green algae: U. prolifera −21.9 to −14.9 Yellow Sea This study Ulva sp. −14.2 to −10.1 New South Wales coast 85 Ulva lactuca −13 to −11 SE Brazil coast 86 −22.5 to −22.3 Mediterranean Sea 87 Ulva intestinalis −12.5 Neva estuary 88 Cladophora glomerata −15.5 to −12.5 Cladophora sp. −20 to −18 Gulf of Mexico 89 Codium sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… δ 13 C (‰) Location Source C3 producers −28.1 ± 2 84 C4 producers −13 ± 1.5 C3 producers −22 to −35 76 C4 producers −11 to −17 Green algae: U. prolifera −21.9 to −14.9 Yellow Sea This study Ulva sp. −14.2 to −10.1 New South Wales coast 85 Ulva lactuca −13 to −11 SE Brazil coast 86 −22.5 to −22.3 Mediterranean Sea 87 Ulva intestinalis −12.5 Neva estuary 88 Cladophora glomerata −15.5 to −12.5 Cladophora sp. −20 to −18 Gulf of Mexico 89 Codium sp.…”
Section: Resultsmentioning
confidence: 99%
“… −19.5 to −16 91 Sargassum sp. −16.3 to −10 New South Wales coast 85 Sargassum vulgare −13 to −12 SE Brazil coast 86 Sargassum sp. −15 to −12.5 Baltic Sea 88 Cystoseira amentacea −19.7 to −15.8 Mediterranean Sea 87 Red algae: Pterocladium capillacea −16.7 to −13.5 New South Wales coast 85 Gelidiella acerosa −19 SE Brazil coast 86 Pterocladiella capillacea −33 to −32 Cryptonemia seminervis −30 Gracilaria sp.…”
Section: Resultsmentioning
confidence: 99%
“…The potential of C. gigas to alter species assemblages has been already widely known (Kochmann et al 2008 ; Markert et al 2009 ; Padilla 2010 ; Green and Crowe 2014 ; Norling et al 2015 ). Comparisons with other native habitat engineers, such as the blue mussel M. edulis , have shown that these changes are dependent on the structural properties of the ecosystem engineer (Buschbaum et al 2006 ; Gain et al 2017 ). Similarities in epifaunal assemblages associated with both C. gigas and O. edulis support these findings and emphasise the importance of the unique biogenic habitat provided by oysters.…”
Section: Discussionmentioning
confidence: 99%
“…Other species interaction may play a major role in determining such species abundance patterns. For example, is it likely that mechanisms interfering with successful recruitments, such as propagule pressure and abundance of grazers disturbing recently settled barnacle larvae or algae seedlings, may vary with time and location, while biological interactions may change with the maturity of oyster reefs (Jenkins et al 2000 ; Holmes et al 2005 ; Rezek et al 2017 ). High densities of C. gigas may also limit the initial abundance of early colonizers such as barnacles possibly by ingestion of larval stages (Troost et al 2008 ), but may prove to be a refuge from predation through the provision of complex three-dimensional structure for matured communities, thereby causing an accumulation of individuals over time (Grabowski 2004 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation